AB1092 High Adherence to Oral Calcium and Vitamin D Supplementation and Bisphosphonate Amongst Patients with Polymyalgia Rheumatica and GIANT Cell Arteritis. (10th June 2014) - Gildberg-Mortensen, R.A.; Jakobsen, S.H.; Lomborg, N.; Just, S.A.; Andreasen, R.A.; Hansen, M.B.; Hansen, I.M.J.
Abstract : Background: Polymyalgia rheumatica (PMR) and Giant Cell Arteritis (GCA) are common inflammatory conditions that almost exclusively affects patients older than 50 years and requires long-term treatment with glucocorticoids (GC). One of the major side-effects of treatment with GC in the long term (>3 month) is the increased risk of developing osteoporosis, leading to an increased risk of bone fracture. Inflammation, reduced mobility and older age which characterizes this group of patients further contributes to an increased risk (1).To prevent loss of bone mass, all of our patients with PMR and GCA are prescribed calcium and vitamin D supplements and depending on the bone density, evaluated with a Dual energy X-ray, additional treatment with bisphosphonate (if T-score <-1). Previous studies show that patients adherence to osteoporosis medication is poor (2, 3). Several factors may contribute to non-adherence including concern of potential side-effects, inconvenience, cost of medication or lack of understanding of the benefits of therapy (3). Objectives: To estimate adherence to oral calcium and vitamin D supplementation as well as bisphosphonate amongst patients with PMR and GCA receiving long-term treatment with GC, and identify factors associated with non-adherence. Methods: We used patient interview to measure compliance in a cross-sectional study. All patients with the diagnosis of PMR and/or GCA registered in our department in December 2013 were identified and contacted by phone, were they answered previous defined questions about medication and adherence. Patient records were examined for medication orders. Results: We identified 118 patients with PMR and/or GCA. 60% were female.117 patients (99.2%) had prescribed calcium and vitamin D and 89.7% of them were adherent to their prescription. Only 2 patients (1.7%) did not take calcium and vitamin D at all and 10 patients (8, 5%) took their medication infrequently, 9 of them 50-100% of the time and 1 patient <50% of the time. 60 patients received additional treatment with bisphosphonate and 91.6% were adherent to this therapy. The remaining 8.4% of the patients did not take the medication at all. Reasons for non-adherence to calcium and vitamin D were forgetfulness in 7 patients (58%), adverse side-effects in 3 (25%) and lack of understanding of treatment benefits in 2 patients (17%). Non-adherence to bisphosphonate was in all cases due to gastro-intestinal side-effects. Conclusions: Contrary to what we expected this study found that adherence to preventative osteoporosis medication in patients with PMR and GCA was high and most frequently patient motivation for non-adherence was forgetfulness and side-effects. Furthermore this study implicates, that adherence to weekly therapy is higher opposed to daily medication. References: N. Duru et al.: EULAR evidence-based and consensus-based recommendations on the management of medium to high-dose glucocorticoid therapy in rheumatic diseases, Annals of the rheumatic diseases. 2013 Dec;72(12):1905-13 Castelo-Branco et al: Treatment persistence and compliance with a combination of calcium and vitamin D, Climateric. 2010 Dec;13(6):578-84 J.A.Cramer et al: A systematic review of persistence and compliance with bisphosphonates for osteoporosis, Osteoporos Int, 2007. Feb;18:1023-31 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3607